Transformation of local cultural values in the modernization of architectural and interior design of traditional market buildings in Bali - Dewi, Ni Made Emmi Nutrisia; Pranajaya, I Kadek; Utami, Ni Kadek Yuni (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Traditional markets in Bali reflect the richness of local culture closely related to people's daily lives. Along with the times and demands for progress, these markets are transforming through the modernization of architectural and interior design. This modernization impacts local cultural heritage, changing how people interact with markets and the traditional values that Balinese people have long upheld. Therefore, research on the transformation of local cultural values in the modernization of architectural and interior design in traditional Balinese markets becomes relevant to understanding the implications and evaluating the preservation and adjustment efforts needed to maintain a unique cultural identity. The main focus is on changes in building design that influence the user experience of the building and the sustainability of cultural heritage as well as providing insight into emerging challenges and opportunities as well as an understanding of efforts to preserve local cultural values. This study will use a qualitative methodology to investigate changes in aesthetic and cultural dimensions. The results of this study demonstrate that cultural values change due to modern buildings being constructed in Bali's traditional marketplaces. The building's modernization has an impact on everyday activities, including the waning of the bargaining culture, the consumer behavior when visiting the upper floors, the traders' behavior regarding the interior conditions of the market, the culture that elevates buyers to the status of kings, and the transactional atmosphere typical of traditional markets. The contribution involves active participation from local communities with solutions in the form of efforts to maintain cultural heritage that can be aligned with implementing innovations that have a positive impact. By involving traders and market owners, solutions can be found to modernize facilities while maintaining local cultural values.